2021
DOI: 10.1007/s00508-021-01928-6
|View full text |Cite
|
Sign up to set email alerts
|

Workability, quality of life and cardiovascular risk markers in aging nightshift workers: a pilot study

Abstract: Summary Background In aging healthcare professionals, multiple stressors such as night work may affect life and work satisfaction and risk for chronic diseases (e.g. cardiovascular disease [CVD]). In this pilot study we compared workability, quality of life (QoL), and CVD risk markers between night shift and day workers. Methods We included 70 hospital employees (mean age 52 ± 4 years, 91.4% female): 32 rotating night shift workers (> 3 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…At the same time, routine interventions aiming to mitigate the onset of such negative out-comes might have a reduced efficacy not focusing on critical mental health predictors and, above all, being usually offered after the exposure to traumatic events [53]. Not surprisingly, fourteen of the twenty-three papers included in our review investigate the conditions of active-duty military personnel and veterans [27][28][29][30], community health agents [31], sworn officers and patrol police officers [36,38], health care professionals [35,[39][40][41]43,49] and caregivers [48]. A further critical issue involving these professionals is the presence of shift work, which has a significant impact on workers' health, QOL, and well-being [49].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At the same time, routine interventions aiming to mitigate the onset of such negative out-comes might have a reduced efficacy not focusing on critical mental health predictors and, above all, being usually offered after the exposure to traumatic events [53]. Not surprisingly, fourteen of the twenty-three papers included in our review investigate the conditions of active-duty military personnel and veterans [27][28][29][30], community health agents [31], sworn officers and patrol police officers [36,38], health care professionals [35,[39][40][41]43,49] and caregivers [48]. A further critical issue involving these professionals is the presence of shift work, which has a significant impact on workers' health, QOL, and well-being [49].…”
Section: Discussionmentioning
confidence: 99%
“…A further critical issue involving these professionals is the presence of shift work, which has a significant impact on workers' health, QOL, and well-being [49]. Indeed, working asocial hours can result in a misalignment in the circadian system and in the sleep-wake cycle, with a consequent increase in the risk for chronic health conditions [40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to other studies, poor quality of sleep was found in night shift nurses compared to day shift nurses. However, rotational shift working among health care providers is necessary to continue care of hospital and residential patients (Jordakieva et al,2022).…”
Section: Literature Reviewmentioning
confidence: 99%